2007
DOI: 10.1021/np070175n
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Structure of Pyranonigrin

Abstract: Fermentation extracts of the marine fungus Aspergillus niger LL-LV3020 were found to have relevant activity in a number of assays. Chemical screening of the extracts revealed that this organism produced numerous secondary metabolites in addition to its principal metabolite, citric acid. The compound with the most significant UV peak was isolated and its structure elucidated. Physical data suggested that this compound is identical with pyranonigrin A (1); however, our structure elucidation led to a different as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 40 publications
4
42
0
1
Order By: Relevance
“…In some instances, such as aspernigrin A, 26, 27 a single HMBC correlation may theoretically differentiate two isomers. However, in cases such as pyranonigrin, 26, 28 spiroleucettadine 29, 30 and almazole D (Table 3), 31, 32 careful consideration of the chemical shift values in the assigned structure may have provided the only clue to the structural misassignment.…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…In some instances, such as aspernigrin A, 26, 27 a single HMBC correlation may theoretically differentiate two isomers. However, in cases such as pyranonigrin, 26, 28 spiroleucettadine 29, 30 and almazole D (Table 3), 31, 32 careful consideration of the chemical shift values in the assigned structure may have provided the only clue to the structural misassignment.…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…3). 24) Pyranonigrin-A has reportedly been isolated from fermentation extract of marine fungus Aspergillus niger (culture LL-LV3020). This study found pyranonigrin-A in the rice mold starter, which is safe and practical for use in food processing, for the first time.…”
Section: Isolation and Identification Of The Antioxidantmentioning
confidence: 99%
“…All structures were elucidated on the basis of extensive 1D and 2D NMR spectroscopic studies ( 1 H, 13 C, COSY, HMQC, HMBC, NOE difference spectra) and MS analysis. For the two chiral pyranonigrin molecules, particularly for pyranonigrin A (C 9 H 10 NO 5 , DBE ¼ 7) 12.34, the absolute configurations were 50 isolated from the marine fungus Aspergillus niger a compound of molecular formula C 9 H 10 NO 5 whose physical data were identical to those published by Hiort et al 49 for pyranonigrin A. Interpretation of the NMR data did not permit the authors 50 to assign structure 12.34a to pyranonigrin A.…”
Section: Revision Of Structures By the Re-examination Of 2d Nmr Datamentioning
confidence: 82%